The Effect of Zam-zam Water to the Lipid Profile (HDL & LDL) at White Mouse (Rattus novergicus) - Tama, Yhang Lidi; Sagiran, Sagiran (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2019)
The estimates from the experts of the World Health Organization (WHO) indicate that 50% of the 12 million world population die from coronary heart disease & blood vessel disease. Low-Density Lipid (LDL) and High-Density Lipid (HDL) ratios are often calculated to estimate the risk of coronary heart disease. Zam-zam water is thought to be efficacious in reducing blood lipid profile levels. This study aims to know the effect of Zam-zam Water on the lipid profile (HDL & LDL) on a white mouse (Rattus Novergicus). The type of this research is an experimental laboratory design with a pre-post control group conducted for 28 days. The subjects of this study were 25 Rattus norvegicus wistar strains, divided into five groups namely control (aquades) group and four treatment groups (concentrations of 25%, 50%, 75% and 100%). The data were obtained by measuring the level of LDL and HDL before and after receiving the treatment of Cholesterol Oxidase Para Aminophenazone (CHODPAP). Also, the data were analyzed using ANOVA test and paired t-test. The Anova analysis showed that the administration of Zam-zam water affected the level of HDL and LDL as proven by the significance of differences among study groups (p <0.05). It is obtained that zam-zam water is 100% proven to have the most influence on HDL and LDL levels. The analysis of paired T-test showed that there were significant differences before and after treatment (p <0.05). Therefore, it can be concluded that the administration of zam-zam water affected the level of HDL and LDL of Rattus norvegicus blood lipid profiles.